Johannes van der Steur's Humanistic Thinking: Efforts to Educate Neglected Children - Pina Dhea Tafana; Rhoma Dwi Aria Yuliantri; Miftahuddin; Adi Yusuf Arrasyid (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study examines the life and humanitarian legacy of Johannes van der Steur, widely known as the â€œFather of Humanityâ€ in Magelang, and analyzes his work through Abraham Maslowâ€™s humanistic theory. Using Kuntowijoyoâ€™s historical method, the research follows five stages: topic selection, heuristics, verification, interpretation, and historiography. Data were collected from personal diaries, biographies, KITLV archives, and historical artifacts. The findings show that Van der Steurâ€™s humanitarian mission was driven by deep concern for abandoned and vulnerable children during the Dutch colonial period. Through the establishment of the Oranje Nassau Orphanage, he developed a systematic approach that addressed childrenâ€™s physiological, safety, social, esteem, and self-actualization needs. Analysis based on Maslowâ€™s hierarchy of needs reveals that Van der Steurâ€™s practices embodied key humanistic principles decades before the publication of A Theory of Human Motivation in 1943. His efforts extended beyond charity by creating a supportive environment that promoted dignity, personal growth, and social integration. This study concludes that Van der Steurâ€™s legacy reflects the humanistic belief in the inherent potential of every individual and demonstrates the transformative role of education and care in fostering self-actualization.